Pengaruh Motivasi Kerja, Kompetensi dan Work Control Terhadap Kinerja Pegawai Di Badan Keuangan Daerah dan Aset Kabupaten Agam - Wela Puspita; Almasdi (Jurnal Ekonomi dan Bisnis Digital, 2022)
This study aims to determine and analyze the effect of work motivation, competence and work control on employee performance in the Agam Regency Regional Financial and Asset Management Agency. This type of research is Expost-Facto research. The population of this study were all employees of the Agam Regency Regional Finance and Asset Management Agency, totaling 52 employees. Sampling was carried out by means of a saturated sample of 52 people. Data was collected using a Likert scale model questionnaire. The data analysis technique is Smart PLS version 3. The results of the study are (1) work motivation has a positive and significant effect on the performance of employees of the Agam Regency Regional Finance and Asset Agency. (2) competence has a positive and significant effect on the performance of employees of the Agami Regency Regional Finance and Asset Agency. (3) work control has a positive and significant effect on the performance of employees of the Agam Regency Regional Finance and Asset Agency. (4) work motivation, competence and work control jointly affect the performance of employees in the Agam Regency Regional Finance and Asset Agency.